Approach to the study of fast electron transport in cylindrically imploded targets. (3rd July 2015) - Del Sorbo, D.; Arikawa, Y.; Batani, D.; Beg, F.; Breil, J.; Chen, H.; Feugeas, J.L.; Fujioka, S.; Hulin, S.; Koga, M.; MacLean, H.; Morace, A.; et al.
Abstract The transport of relativistic electron beam in compressed cylindrical targets was studied from a numerical and experimental point of view. In the experiment, cylindrical targets were imploded using the Gekko XII laser facility of the Institute of Laser Engineering. Then the fast electron beam was created by shooting the LFEX laser beam. The penetration of fast electrons was studied by observing Kα emission from tracer layers in the target.